A Study on the Growth of Almarai as a Corporate Citizen in the era that seeks Sustainable - Vinodkumar, Nisa; Meharunisa, Sayeda; Sulphey (International Journal of Psychosocial Rehabilitation, 2020)
Sustainable development (SD) is now an essential aspect, which has wide applicability in almost all fields. It has the ability to enhance competitiveness and protect the rights of various stakeholders. Organizations have been adopting various strategies to enhance human capital and natural resources for future requirements. Businesses have been making a difference across a broad spectrum through SD, corporate social responsibility (CSR), and corporate citizenship (CC). This has helped in ensuring enhanced profitable and sustainable growth with higher societal benefits. The study intended to report the best practices in CSR and CC in Almarai, a Saudi Arabian conglomerate, for the past 10 years and to understand its growth strategy in moving from mere CSR to creating shared value through SD and its emergence as a corporate citizen in the business world. The study assesses the strategy of creating value for its stakeholders through addressing their varied needs and challenges. Using the published data of Almarai, the study assesses the extent of the organization’s commitment towards CSR, the extent to which it is integrated in their corporate policies, and the nature and scope of the firms’ CSR activities.It also addresses the relation of CSR to its economic, environmental, and business responsibilities. Results indicate a high level of commitment and involvement towards CSR, CC, and SD.